Investigating the cardiac pathology of SCO2‐mediated hypertrophic cardiomyopathy using patients induced pluripotent stem cell–derived cardiomyocytes. Issue 2 (28th November 2017) - Hallas, Tova; Eisen, Binyamin; Shemer, Yuval; Ben Jehuda, Ronen; Mekies, Lucy N.; Naor, Shulamit; Schick, Revital; Eliyahu, Sivan; Reiter, Irina; Vlodavsky, Eugene; Katz, Yeshayahu (Shai); Õunap, Katrin; et al.
Abstract: Mutations in SCO2 are among the most common causes of COX deficiency, resulting in reduced mitochondrial oxidative ATP production capacity, often leading to hypertrophic cardiomyopathy (HCM). To date, none of the recent pertaining reports provide deep understanding of the SCO2 disease pathophysiology. To investigate the cardiac pathology of the disease, we were the first to generate induced pluripotent stem cell (iPSC)‐derived cardiomyocytes (iPSC‐CMs) from SCO2‐mutated patients. For iPSC generation, we reprogrammed skin fibroblasts from two SCO2 patients and healthy controls. The first patient was a compound heterozygote to the common E140K mutation, and the second was homozygote for the less common G193S mutation. iPSC were differentiated into cardiomyocytes through embryoid body (EB) formation. To test the hypothesis that the SCO2 mutation is associated with mitochondrial abnormalities, and intracellular Ca 2+ ‐overload resulting in functional derangements and arrhythmias, we investigated in SCO2‐mutated iPSC‐CMs (compared to control cardiomyocytes): ( i ) the ultrastructural changes; ( ii ) the inotropic responsiveness to β‐adrenergic stimulation, increased [Ca 2+ ]o and angiotensin‐II (AT‐II); and ( iii ) the Beat Rate Variability (BRV) characteristics. In support of the hypothesis, we found in the mutated iPSC‐CMs major ultrastructural abnormalities and markedly attenuated response to the inotropic interventions and caffeine, as well as delayed afterdepolarizations (DADs) and increased BRV, suggesting impaired SR Ca 2+ handling due to attenuated SERCA activity caused by ATP shortage. Our novel results show that iPSC‐CMs are useful for investigating the pathophysiological mechanisms underlying the SCO2 mutation syndrome.